Optimization method for proteomic analysis of the larva and adult tissues of Plutella xylostella (L.) (Lepidoptera: Plutellidae) - Maizom Hassan; Norazila Yusoff; Wan Mohd Aizat; Nurul Wahida Othman; Idris Abd Ghani (Penerbit Universiti Kebangsaan Malaysia, 2018)
Plutella xylostella (L.) (Lepidoptera: Plutellidae), the major insect pest of cruciferous crops worldwide shows significant resistance to almost all classes of insecticides. In order to effectively prevent and manage the insecticidal resistance, it is crucial to understand the physiological adaptation of insects against insecticides. Identification of insect protein that interacting with insecticides and characterization of their modification in resistant strains can be done by using differential proteomics approach. This study focuses on optimizing a sensitive and rapid method for the extraction of high quality protein of both larva and adult tissues of P. xylostella to be used in two-dimensional gel electrophoresis. Five extraction methods were evaluated for protein concentration, yields and resolving patterns of one-dimensional and two-dimensional electrophoresis. The results showed that trichloroacetic acid/acetone extraction methods with two different concentrations of 2-mercaptoethanol produced the highest protein concentration and yield for both adult and larva tissues, respectively. Meanwhile, trichloroacetic acid/acetone with dithiothreitol extraction method gave better separation of spots and intensity for both larva and adult tissues compared to other methods tested. As such, we concluded that trichloroacetic acid/acetone with dithiothreitol successfully yielded high total protein concentration and good separation of two-dimensional electrophoresis gel spots in both adult and larva P. xylostella.